Fault Detection of Electrical Machines Rolling Element and Prediction through AI (Pakistan Journal of Scientific Research, 2022)
The research examines how Artificial Intelligence (AI) and machine learning can identify a minor rolling element problem (hole and scratch). Keeping track of a machine's health makes it possible to spot problems before they become costly, unscheduled production process shutdowns. In the study, a multi-stage decision mechanism was built using the convolution neural network (CNN) model.
Keywords: Rolling element fault; ANN; Kurtosis; MATLAB; Dataset